Smart Home Using Internet of Things - S, Keerthana; H, Meghana; R, Priyanka K; Rao, Sahana V; N, Ashwini B (Perspectives in Communication, Embedded-systems and Signal-processing - PiCES, 2017)
Home automation or smart home is the residential extension of building automation. There are various types of automation based on the application they can be categorized as home automation, industrial automation, autonomous automation, building automation, etc. This system uses Wi-Fi for remote monitoring and are a part of the Internet of things. Modern systems generally consist of switches and sensors connected to a central hub sometimes called a "gateway" from which the system is controlled with a user interface that is interacted either with a wall-mounted terminal, mobile phone software, tablet computer or a web interface, often but not always via internet cloud services. In this work, CC3200MCU is used which has in built Wi-Fi module and temperature sensor. The sensed temperature data is send to MCU and then it is posted to the server, status of the fan and light is viewed in the android application and then it is controlled with the same.